Ultra-fast high-temperature sintering of strontium titanate. (1st June 2022) - Mishra, Tarini Prasad; Wang, Shufan; Lenser, Christian; Jennings, Dylan; Kindelmann, Moritz; Rheinheimer, Wolfgang; Broeckmann, Christoph; Bram, Martin; Guillon, Olivier
Abstract: Ultrafast High-temperature Sintering (UHS) is a novel sintering process enabling extremely high heating rates by direct contact of sample to electrically heated thin carbon strips. Using strontium titanate as a model system, the densification behavior by UHS was investigated. Controlled experiments via maximum current limitation were used to study the influence of the applied current on the degree of densification and resulting final grain size. Simulations by Finite Element Modeling (FEM) allow estimating the sample temperature reached during UHS, which is in good agreement with the experimental data. Moreover, the FEM simulations show a self-stabilization of the sample temperature by thermal radiation. UHS results suggest that rapid densification can be achieved with an extremely high heating rate. The microstructure of the undoped strontium titanate samples shows exaggerated grain growth and pore-boundary separation, which results in pore entrapment inside grains. The addition of 2 mol% iron in strontium titanate is beneficial by limiting the grain growth during the UHS sintering cycle. Uniform densification and grain growth in the sample is consequently observed. Scanning transmission electron microscopy/energy dispersive x-ray spectroscopy (STEM/EDS) is utilized to analyze grain boundary segregation. Measurement of the electrical conductivity of the UHS sintered samples by impedance spectroscopy suggest that rapid densification by UHS enables full access to the functional properties of strontium titanate as compared to the conventionally sintered material. Graphical abstract: Image, graphical abstract